Penyuluhan Kewirausahaan Untuk Memberikan Identitas Bagi Kelompok UMKM di Desa Srimukti - Yayan Hendayana; Salsabila Taqwaning Afifi; Fadila Kurniasih; Anna Wijayanti; Ivan Ardiansyah; Dwi Putri Aprillia; Putri Mutiara; Damar Asmarani; Franco Nero Rupelu; Rido Akbar; Muhammad Dzaky (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This community service by the service team was carried out for the implementers of Group 3 Community Service Program at Bhayangkara University, Jakarta Raya. This was done for MSME actors in Srimukti Village who had not been touched by forums and even the UMKM service. The majority of the livelihoods of the people of Srimukti village are farmers, some of the people of Srimukti village also have businesses that are classified as Micro, Small and Medium Enterprises (MSMEs) such as barbershops, stalls. This counseling and mentoring activity is targeted at MSME actors in Srimukti Village. This counseling and mentoring aims to motivate people to continue entrepreneurship and the importance of branding. Counseling according to is an explanation that emphasizes a certain object and the expected result is a change in the behavior of individuals or groups of people. Defines entrepreneurship as the ability to create something new and different. With entrepreneurship, in addition to having the opportunity to generate large income for entrepreneurs, it is also able to reduce the number of unemployed (Budy, 2017). According to branding is a name, term, sign, symbol, design or a combination of all that is intended to identify goods or services or groups of sellers and to differentiate from competing goods or services. This study uses qualitative, data analysis by observing and interviewing. The implementation of community service for MSMEs in Srimukti Village was carried out directly starting with counseling, namely approaching every business actor and then explaining the purpose of our team in holding this work program to advance MSMEs in Srimukti Village, explaining how important it is to have branding to prepare for business competition and shape public perception. After that, our team collected data and provided motivation to MSME business actors. Entrepreneurial motivation was conveyed with the aim that MSMEs in Srimukti Village could be motivated to grow their businesses even bigger.